Hypoxia-induced LncRNA-BX111 promotes metastasis and progression of pancreatic cancer through regulating ZEB1 transcription. Issue 44 (1st November 2018) - Deng, Shi-jiang; Chen, Heng-yu; Ye, Zeng; Deng, Shi-chang; Zhu, Shuai; Zeng, Zhu; He, Chi; Liu, Ming-liang; Huang, Kang; Zhong, Jian-xin; Xu, Feng-yu; Li, Qiang; et al.
Abstract The contribution of long noncoding RNAs (lncRNAs) to pancreatic cancer progression and the regulatory mechanisms of their expression are attractive areas. In the present study, the overexpression of lncRNA-BX111887 (BX111) in pancreatic cancer tissues was detected by microarray and further validated in a cohort of pancreatic cancer tissues. We further demonstrated that knockdown or overexpression of BX111 dramatically repressed or enhanced proliferation and invasion of pancreatic cancer cells. Mechanically, BX111 activated transcription of ZEB1, a key regulator for epithelia-mesenchymal transition (EMT), via recruiting transcriptional factor Y-box protein (YB1) to its promoter region. Moreover, we revealed that BX111 transcription was induced by hypoxia-inducible factor (HIF-1α) in response to hypoxia. In addition, BX111 contributed to the hypoxia-induced EMT of pancreatic cells by regulating expression of ZEB1 and its downstream proteins E-cadherin and MMP2. Coincidence with in vitro results, BX111 depletion effectively inhibited growth and metastasis of xenograft tumor in vivo. The clinical samples of pancreatic cancer further confirmed a positive association between BX111 and ZEB1. Moreover, high BX111 expression was correlated with late TNM stage, lymphatic invasion and distant metastasis, as well as short overall survival time in patients. Taken together, our findings implicate a hypoxia-induced lncRNA contributes to metastasis and progression of pancreatic cancer, and suggest BX111 might be applied as a potential biomarker and therapeutic target for pancreatic cancer.